THE ROLE OF PEERS IN IMPROVING SELF-EFFICACY OF STUDENTS' CONFIDENCE IN PRIMARY SCHOOL - Khotimah, Sonia Puji Nur; Azizah, Wahyu Sukma Nur; Ulum, Siti Raudhatul; Nengsih, Luluk Wahyu (Sindoro: Cendikia Pendidikan, 2024)
Elementary School (SD) is like a golden period for children. In this phase, they not only experience a rapid surge in cognitive and social abilities, but it is also a crucial moment for growing self-efficacy or self-confidence. Self-efficacy, which is defined as an individual's belief in their ability to complete tasks and achieve goals, is an important aspect that needs to be developed at this time. This self-confidence is like a solid foundation that will support the child's success in the future. Therefore, this study aims to analyze in depth how positive interactions with peers can increase elementary school students' self-efficacy. It is hoped that this research will provide new insight into the importance of the role of peers in children's development, especially in building self-efficacy. The results of this research can later be used to develop more effective and student-centered learning strategies, optimally involving the role of peers. Based on research results, peers are proven to have a crucial role in growing self-efficacy or self-confidence in elementary school students. Peers are like pillars of support who provide support, encouragement and motivation for students to develop. Based on the results of literature research, it was concluded that the role of peers needs to be optimized to increase elementary school students' self-efficacy. Teachers and parents need to create a conducive learning environment where students can interact positively with their peers.